2007
DOI: 10.1074/jbc.m703388200
|View full text |Cite
|
Sign up to set email alerts
|

Helix 8 Leu in the CB1 Cannabinoid Receptor Contributes to Selective Signal Transduction Mechanisms

Abstract: The intracellular C-terminal helix 8 (H8) of the CB 1 cannabinoid receptor deviates from the highly conserved NPXXY(X) 5,6 F G-protein-coupled receptor motif, possessing a Leu instead of a Phe. We compared the signal transduction capabilities of CB 1 with those of an L7.60F mutation and an L7.60I mutation that mimics the CB 2 sequence. The two mutant receptors differed from wild type ( 2؉ current inhibition by WIN-55,212-2 were reduced in the mutants. Reconstitution experiments with pertussis toxin-insensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 58 publications
(97 reference statements)
2
80
0
Order By: Relevance
“…Previous work demonstrated differential association of distinct Ga i/o subtypes with CB 1 Rs occupied by different ligands (Mukhopadhyay and Howlett, 2005) and differential abilities of different ligands to activate purified G i versus G o (Glass and Northup, 1999). In addition, different Ga i/o subtypes interact selectively with either the C-terminus or third intracellular loop of the CB 1 R (Mukhopadhyay and Howlett, 2001;Anavi-Goffer et al, 2007), so CRIP 1a association with the CB 1 R Cterminus (Niehaus et al, 2007) might differentially interfere with G-protein association with these distinct intracellular domains of the CB 1 R. Because the C-terminus serves as a docking site for multiple protein-protein interactions (Howlett et al, 2010;Smith et al, 2010), the effects of CRIP 1a on CB 1 R-G-protein interactions might depend on both ligand occupancy of the receptor and the presence of additional interacting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated differential association of distinct Ga i/o subtypes with CB 1 Rs occupied by different ligands (Mukhopadhyay and Howlett, 2005) and differential abilities of different ligands to activate purified G i versus G o (Glass and Northup, 1999). In addition, different Ga i/o subtypes interact selectively with either the C-terminus or third intracellular loop of the CB 1 R (Mukhopadhyay and Howlett, 2001;Anavi-Goffer et al, 2007), so CRIP 1a association with the CB 1 R Cterminus (Niehaus et al, 2007) might differentially interfere with G-protein association with these distinct intracellular domains of the CB 1 R. Because the C-terminus serves as a docking site for multiple protein-protein interactions (Howlett et al, 2010;Smith et al, 2010), the effects of CRIP 1a on CB 1 R-G-protein interactions might depend on both ligand occupancy of the receptor and the presence of additional interacting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with cB1 receptor internalization studies in the presence of pTX in hippocampal neurons and cB1 receptor-transfected cells, 28,29 and with a study that uses cB1 receptor mutants that are able to internalize whereas g-protein sequestration is impaired. 37 pTX might affect the efficacy of the receptor-β-arrestin interaction and the receptor internalization process. Minor effects of pTX on β-arrestin recruitment were also found for the EDg1 receptor, 38 c5a receptor, and cXcr2 receptor in pathHunter EFc cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have demonstrated that structurally distinct ligands regulate CB 1 receptor-G protein complexes with Ga i 1, Ga i 2, and Ga i 3 such that multiple conformations of the receptor can be evoked by ligands to regulate individual G proteins Howlett, 2001, 2005;Anavi-Goffer et al, 2007). Mukhopadhyay and Howlett, (2005) found that the nonhydrolyzable GTP analog, GTPgS, promoted complete dissociation of all CB 1 receptorGa i complexes; the CB 1 agonist desacetyllevonantradol precluded GTPgS-induced dissociation of Ga i 3, while leaving Ga i 1 dissociation unaffected.…”
Section: Effect Of Allosteric Modulators On Cb 1 Receptor Agonist Binmentioning
confidence: 99%
“…It is now accepted that a single receptor may engage different signaling pathways and that various ligands might influence these pathways differentially (Galandrin et al, 2007). This relatively new concept is termed "functional selectivity" (Baker and Hill, 2007;Kenakin, 2007) and has been described for the CB 1 receptor (Glass and Northup, 1999;Mukhopadhyay and Howlett, 2001;Anavi-Goffer et al, 2007). This term can also be applied to allosteric modulators.…”
Section: Introductionmentioning
confidence: 99%